2017
DOI: 10.14202/vetworld.2017.380-385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of fermented fish silage on serum biochemical parameters of broiler Japanese quails (Coturnix coturnix japonica)

Abstract: Aim:The objective of this study was to evaluate the effect of feeding fermented fish silage (FFS) on serum biochemical parameters of Japanese quails (Coturnix coturnix japonica).Materials and Methods:A total of 192, 7-day-old broiler Japanese quail chicks of either sex, were randomly distributed into four dietary treatments with four replicates in each group having 12 chicks in each replicate pen. The dietary treatments were T1 – Control diet, T2 – Diet containing 5% FFS, T3 – Diet containing 10% FFS, and T4 –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(15 reference statements)
2
7
1
Order By: Relevance
“…Our average and minimal-maximal values of AST were similar to these obtained from Scholz et al (2009) in Japanese quails and from Gylstorff and Grimm (1998) in doves. Unlike cited studies and our results Nazifi and Asasi (2001), Hamidipour et al (2016), Sokół et al (2015), Panda et al (2017) and Abang et al (2017) found significantly lower values of AST in Japanese quails. Such lower values of AST were reported from Albokhadaim et al (2013) in local chickens from Saudi Arabia and Abou-Shehema et al (2016) in Bandarah chickens.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our average and minimal-maximal values of AST were similar to these obtained from Scholz et al (2009) in Japanese quails and from Gylstorff and Grimm (1998) in doves. Unlike cited studies and our results Nazifi and Asasi (2001), Hamidipour et al (2016), Sokół et al (2015), Panda et al (2017) and Abang et al (2017) found significantly lower values of AST in Japanese quails. Such lower values of AST were reported from Albokhadaim et al (2013) in local chickens from Saudi Arabia and Abou-Shehema et al (2016) in Bandarah chickens.…”
Section: Discussioncontrasting
confidence: 95%
“…Similar results were found from Sokół et al (2015) in quails with experimental coccidiosis treated with toltrazuril. The values of ALT reported by Mnisi et al (2017) in 9 week old male Japanese quails, Hamidipour et al (2016) and Panda et al, (2017) in the same bird species were in line with our results. These differences can be explained with the different productive types of the experimental birds and the used laboratory equipment, diagnostics and methodology.…”
Section: Discussionsupporting
confidence: 93%
“…Serum biochemical profile reflects nutritional, physiological, and pathological status of an individual ( 18 – 20 ). Biochemical parameters are inter-related with different body functions and alteration.…”
Section: Introductionmentioning
confidence: 99%
“…The surface tension (γ) of polymer solution was determined by using the capillary-rise method, one advantage of this method is the absence of weightiness of polymer solution, which is not possible for measuring tiny quantity of polymers. Mathematically (γ) is given by the following expression [16]:…”
Section: Resultsmentioning
confidence: 99%